Peningkatan kemampuan pemecahan masalah matematik siswa melalui pembelajaran dengan menggunakan metode drill - Kurniawan, Yunda (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
Students’ poor mathematic problem-solving ability is an important problem in mathematic. In enriching students’ ability, it is needed an effort for students to solve the items regularly. The alternative method that can be used is drill method. This research aimed to know the improvement of students’ ability in mathematic problem solving by using the drill and the students’ attitude. This research was the quasy experiment with randomized pre-test post-test control group design. The experiment class used drill method. The research subjects were the students of Manba Ul’ulum, Tangerang city, Banten Regency. The result of this research showed that the improvement of students’ mathematic problem-solving by using drill method was better than the conventional learning. The main gain for the experimental and control class included to the high category. The positive attitude was also shown in the learning process by using drill method.